SNR: Say No To Corruption Application - Anti-Corruption Education Towards Corruption Prevention Efforts at UTHM - Mohd Zahari, Dang Sofia; Ab Halim, Fazlinda (Research and Innovation in Technical and Vocational Education and Training, 2025)
SNR, which stands for Say No to Corruption, is a 2D animated Android application aimed at promoting ethical behavior, integrity, and anti-corruption education. SNR was developed to provide deeper education and knowledge about corruption issues among students and staff at UTHM, to promote anti-corruption. This study further elaborates on the content, design, and functionality of the application, as well as the benefits of text, sound, animation, and video in providing a clear and engaging learning experience. The development of the SNR anti-corruption educational application utilizes the ADDIE model, which consists of five (5) phases: the analysis phase, the design phase, the development phase, the implementation phase, and the testing phase. Additionally, the development of the application employs Adobe Animate and Adobe Illustrator software. Moreover, the application was evaluated based on interface design, interaction design, and content design by three (3) multimedia experts and one (1) content expert. Following testing, the application was accepted by the experts, with most agreeing on the application's design. Multimedia experts gave the application a score of 80%. Multimedia experts 2 gave it a score of 82% and multimedia experts 3 gave it a score of 85%. Content experts gave it a score of 90% satisfaction with the content of the application. Improvements were made to maximize the application. Ultimately, the developed application successfully achieved its development objectives and met its goals.